2008
DOI: 10.1074/jbc.m707974200
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Dimethylation of Histone H4 Lysine 20 by Suv4-20

Abstract: Post-translational modifications of histone tails direct nuclear processes including transcription, DNA repair, and chromatin packaging. Lysine 20 of histone H4 is mono-, di-, or trimethylated in vivo, but the regulation and significance of these methylations is poorly understood. The SET domain proteins PRSet7 and Suv4-20 have been implicated in mono-and trimethylation, respectively; however, enzymes that dimethylate lysine 20 have not been identified. Here we report that Drosophila Suv4-20 is a mixed product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
142
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(154 citation statements)
references
References 47 publications
12
142
0
Order By: Relevance
“…Trimethylated H4K20 is associated with repressed chromatin because it is targeted to constitutive heterochromatin, various repetitive elements, and imprinting control regions (16,18,19). Dimethylated H4K40 is more widely distributed within euchromatic regions in the genome, and recent findings suggest that it may function to recruit the 53BP1 repair protein to sites of DNA damage (17,20,21).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Trimethylated H4K20 is associated with repressed chromatin because it is targeted to constitutive heterochromatin, various repetitive elements, and imprinting control regions (16,18,19). Dimethylated H4K40 is more widely distributed within euchromatic regions in the genome, and recent findings suggest that it may function to recruit the 53BP1 repair protein to sites of DNA damage (17,20,21).…”
mentioning
confidence: 99%
“…Trimethylated H4K20 is associated with repressed chromatin because it is targeted to constitutive heterochromatin, various repetitive elements, and imprinting control regions (16,18,19). Dimethylated H4K40 is more widely distributed within euchromatic regions in the genome, and recent findings suggest that it may function to recruit the 53BP1 repair protein to sites of DNA damage (17,20,21).The PR-Set7 enzyme is responsible for the bulk of H4K20 monomethylation (22)(23)(24)(25). Although original observations suggested that this modification was associated with repressed regions of the genome, recent findings have identified monomethylated H4K20 within actively transcribed genes (26,27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro binding of H4K20Me 1 or H4K20Me 2 over H3K36Me 2 or other histone tail modifications associated with gene activation presented in this study strongly points to the N terminus of histone H4 being the likely in vivo binding target for the MSL3 and MRG15 CBDs. Supporting a role for H4K20Me 1 in the recruitment of the MSL complex, H4K20Me 1 is an abundant modification on histone tails in Drosophila and humans, and its presence correlates positively with the level of transcriptional activity along human genes, at least as well as for H3K36Me 3 (59,(62)(63)(64)(65)(66)(67). Furthermore, other studies have shown that H4K20Me 1 is found to be preferentially deposited on nucleosomes residing within exons (68,69), a pattern mirrored in the X-chromosome binding of the Drosophila MSL complex (30).…”
Section: Msl3 Cbd Function In Msl Hat Complex Targeting and Dosagementioning
confidence: 99%
“…54 In agreement with these results, it has very recently been shown that SUV420H1 and SUV420H2 are the enzymes responsible for the ubiquitous dimethylation of H4K20 in human and Drosophila melanogaster cells and that depletion of both SUV420H1 and SUV420H2 by siRNA decreases the number of 53BP1 foci in HeLa cells. 55 Another report describes the role of H4K20me during NHEJ in mammals, whereby during the process of XRCC4-dependent NHEJ, 53BP1 recruitment depends on its interaction with dimethylated H4K20 but not on H2AX. 23 The same study also found that, alternatively, MDC1 mediates efficient HR/SCR (sister-chromatid recombination) in a manner strictly dependent on its ability to recruit γH2AX and does not require recruitment of 53BP1 or BRCA1.…”
Section: Chromatin Remodeling Activities During Dna Repairmentioning
confidence: 99%